Familial gout and renal failure. Issue 9 (September 1981) - Warren, D J; Simmonds, H A; Gibson, T; Naik, R B
Abstract : Clinical gout and renal failure was seen in a 9-year-old girl. The family tree showed that 9 out of 11 young females in three generations suffered from hyperuricaemia and normal (n = 1), or impaired (n = 8), renal function. One set of twins occurred in each generation and there is only one living male subject. In members with renal failure there was no improvement in renal function after treatment of hyperuricaemia, and in 2 sisters oral contraceptives appeared to precipitate hypertension. This clinical picture may be more common than is generally realised because of failure to compare blood uric acid values with suitable age- and sex-matched controls. The evidence from this family suggests that hyperuricaemia preceded the development of renal failure.